2006
DOI: 10.1128/jvi.01334-06
|View full text |Cite
|
Sign up to set email alerts
|

Latency-Associated Nuclear Antigen of Kaposi's Sarcoma-Associated Herpesvirus Recruits Uracil DNA Glycosylase 2 at the Terminal Repeats and Is Important for Latent Persistence of the Virus

Abstract: Latency-associated nuclear antigen (LANA) of KSHV is expressed in all forms of Kaposi's sarcomaassociated herpesvirus (KSHV)-mediated tumors and is important for TR-mediated replication and persistence of the virus. LANA does not exhibit any enzymatic activity by itself but is critical for replication and maintenance of the viral genome. To identify LANA binding proteins, we used a LANA binding sequence 1 DNA affinity column and determined the identities of a number of proteins associated with LANA. One of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 76 publications
0
36
0
Order By: Relevance
“…It must be noted that this model as proposed adds to the previous model where LANA directly binds to TRs at LBSs (12). Like H2AX, another human protein uracil DNA glycosylase 2 (UNG2) has previously been shown to contribute to the LANA-TR binding at the C terminus of LANA (30).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…It must be noted that this model as proposed adds to the previous model where LANA directly binds to TRs at LBSs (12). Like H2AX, another human protein uracil DNA glycosylase 2 (UNG2) has previously been shown to contribute to the LANA-TR binding at the C terminus of LANA (30).…”
Section: Discussionmentioning
confidence: 78%
“…Chromatin immunoprecipitation (ChIP) was carried out as has been described earlier (24,30). Briefly, after the cells were fixed, nuclei were isolated and sonicated in the nuclear lysis buffer to an average DNA length of 700 bp, as confirmed by agarose gel electrophoresis.…”
Section: Methodsmentioning
confidence: 99%
“…However, HSV-1 reactivation was measured post-explant from trigeminal ganglia: a tissue composed of terminally differentiated adult neurons with low levels of host UNG (18,36). Reactivation is also reduced in human gammaherpesvirus latency cell systems lacking the EBV viral UNG (BKRF3) alone or in the absence of both the vUNG and the host UNG (13,18,(37)(38)(39). Interestingly, Su et al (13) recently reported that host UNG2 levels decrease as EBV reactivation proceeds, indicating that the viral UNG is needed to promote replication under conditions of low host UNG levels (13).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, recent studies with Kaposi's sarcoma herpesvirus identified human UNG2 as a protein interacting with latencyassociated nuclear antigen. Depletion of UNG2 in Kaposi's sarcoma herpesvirus-positive cells by using siRNA reduced the number of viral genome copies and produced infection-deficient virus (73). Because UNG2 was previously found to interact with several cellular replication proteins, such as PCNA, PRA, and polymerase ␣ (29,50,63), it would be interesting to study whether UNG2 can recruit these cellular machineries to the viral replication compartment for enhancing viral replication efficiency.…”
Section: Discussionmentioning
confidence: 99%